Equal pay in lifts? 1918 (1918)
1918 1918-1939 "Equal pay in lifts? 1918" [EP0063], 1918 These press cuttings from 1918 show concern that the success of the bus and tram workers' strike might encourage agitation for equal pay in other sectors. Lift operators in government offices were threatening to strike for equal pay.